DECISION-MAKING SUPPORT SYSTEM TO SUPPORT OF SOCIAL NETWORKS USERS BASED SIMILAR COMMON INTERESTS AND PREFERENCES (Computer systems and information technologies, 2022)
Today, the socialization of individuals with common interests is an extremely important process in the isolation of people due to the prolongation of the global pandemic. At the same time, most people are always trying to simplify and automate all the basic life processes that usually take up a lot of free time. The same applies to the process of socialization of the individual. Machine learning and SEO technologies are currently extremely important in the context of IS development and big data analysis. Virtually every IP popular among a large number of people uses appropriate socialization mechanisms. The main function of the IS of socialization of individuals by common interests is to find relevant users, so the main task is to write an optimized algorithm that automates the process of socialization of users. In this case, a special algorithm was created based on algorithms such as Levenstein's algorithm, sample extension, N-grams and the Noisy Channel model.
Keywords: social network; convolutional neural network; siamese neural network; Levenshtein distance; Noisy Channel model; fuzzy search